Development of external dosimetry audits for advanced technology in radiotherapy dose delivery: An IAEA coordinated research project. (September 2016) - Izewska, J.; Wesolowska, P.; Lechner, W.; Georg, D.; Tomsej, M.; Followill, D.; Kry, S.; Tenhunen, M.; Povall, J.; Thwaites, D.
Abstract : Introduction and purpose: An IAEA co-ordinated research project (CRP) is under implementation that develops methodology for remote dosimetry audits of IMRT techniques to be offered to radiotherapy centres by national audit networks in low and middle income countries. Materials and methods: The CRP involves four audit steps: (i) remote verification of TPS calculation of small beam output factors relevant to IMRT (ii) dosimetry audit of MLC positional performance for IMRT using radiochromic film, (iii) film audit of single clinical IMRT field dose delivery and (iv) 'end-to-end' dosimetry audit for multiple field IMRT techniques using TLDs and radiochromic films. New procedures, phantoms, instructions and data sheets for audited centres were developed at the IAEA and tested through multinational pilot studies. Research groups from 14 countries participate in the CRP. Results: The results of the first CRP step show agreement within 1% of participants' TPS output factors and the reference data for field sizes ⩾4 × 4 cm 2 but dose overestimation by TPSs by 2–3% for field sizes ⩽3 × 3 cm 2 . The second step confirmed that most audited MLCs perform as expected. The results of the third CRP step show that TPS plans prepared by participants and delivered to films agree well; however, comparison of gamma analysis techniques highlighted differences among centres. The fourth step 'end-to-end' IMRT audit is on-going. Conclusion: A four step methodology for remote dose audits of IMRT and related beam characteristics has been developed at the IAEA and is being tested before dissemination to national audit networks operating across the world. Disclosure: No conflicts of interest.